2019
DOI: 10.3390/catal9020197
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Influence of Cobalt Oxides Valence State Change for C6H5COOH Pyrolysis

Abstract: Benzoic acid (C6H5COOH) is selected as coal-based model compound with Co compounds (Co3O4, CoO and Co) as the catalysts, and the influence of the valence state change of the catalyst for pyrolysis process is investigated using density functional theory (DFT). DFT results shows that the highest energy barrier of C6H5COOH pyrolysis is in the following order: Ea(CoO) <Ea(Co3O4) <Ea(no catalyst) <Ea(Co). In general, Co3O4 catalyst accelerates C6H5COOH pyrolysis. Then, the catalytic activity further increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…studied the effect of Co compounds (Co 3 O 4 , CoO and Co) on coal catalytic pyrolysis using benzoic acid (C 6 H 5 COOH) as a model compound of coal. They investigated the influence of the valence state change of the catalyst for coal pyrolysis process using DFT calculations [9]. The results showed that the energy barrier of C 6 H 5 COOH pyrolysis followed in the order: Ea(CoO) < Ea(Co 3 O 4 ) < Ea(blank) < Ea(Co).…”
mentioning
confidence: 99%
“…studied the effect of Co compounds (Co 3 O 4 , CoO and Co) on coal catalytic pyrolysis using benzoic acid (C 6 H 5 COOH) as a model compound of coal. They investigated the influence of the valence state change of the catalyst for coal pyrolysis process using DFT calculations [9]. The results showed that the energy barrier of C 6 H 5 COOH pyrolysis followed in the order: Ea(CoO) < Ea(Co 3 O 4 ) < Ea(blank) < Ea(Co).…”
mentioning
confidence: 99%